Level of Understanding of HPV Vaccine as Cervical Cancer Prevention at Ulin Hospital - Setyo Teguh Waluyo; Ferry Armanza; Hariadi Yuseran; Kevin Stanley Halim; Daniel Paranatha Lumban Gaol; Yakob Togar (Lambung Mangkurat University, 2023)
Cervical cancer is one of the most common cancers in women worldwide. HPV (Human Papilloma Virus) vaccination is approved by the WHO (World Health Organization) as a prevention method for cervical cancer. This research aims to determine the level of knowledge, attitudes, and behaviors of the community in Banjarmasin, specifically around RSUD Ulin, regarding HPV vaccination as a prevention method for cervical cancer. The study was conducted using a cross-sectional design at RSUD Ulin, Banjarmasin, South Kalimantan. The study population consisted of productive-age patients who came for treatment at RSUD Ulin Banjarmasin. Data were collected using quota sampling technique. The questionnaire consisted of 4 major sections: the first part contained socio-demographic information (8 questions), the second part focused on knowledge level (21 questions), the third part assessed attitudes (12 questions), and the fourth part covered practices (7 questions). The results revealed a total sample of 150 women aged between 20 to 62 years with an average age of 33.46 ± 9.69 years. Out of the 150 research subjects, it was found that 67 women (44.7%) had high knowledge, 96 women (64%) had positive attitudes, and 79 women (52.7%) exhibited positive behaviors. Therefore, enhancing public knowledge about HPV vaccination is likely to have a positive impact on patients' attitudes and behaviors towards HPV vaccination